Study of Organic Micropollutants Degradation by Atmospheric Pressure Plasma - Phang Sheng Shan,; Cha Kai Quan,; Roslan, Muhammad Sufi (Multidisciplinary Applied Research and Innovation, 2024)
This study is about the removal of organic micropollutants by atmospheric pressure plasma as effect of micropollutants to the environment and living things is severe. In this writing, the effect of reactive oxygen and nitrogen on organic micropollutants is investigated to degrade it. Organic micropollutants used in this study are methylene blue and phenol. Both samples are going through plasma treatment in a treatment beaker consisting of two electrodes, one at bottom and another one on the surface of water sample. The micropollutants are degraded by the reactive free radicals generated by plasma. The treated samples show a decrease in micropollutants after the analysis of Fourier-transform infrared spectroscopy (FTIR) and Ultraviolet–visible spectroscopy (UV-Vis). The plasma treatment is unable to degrade all of the micropollutants in 30 seconds but it able to decrease the concentration of micropollutants. Therefore, plasma treatment is a reliable method and should be included in the stages of water treatment